Nonlinear maps from closed-loop tandems of A-to-D and D-to-A converters - Edang, Arthur E. (Animo Repository, 2011)
A new class of dynamical maps arises from tandems consisting of an analog-to-digital converter and a digital-to-analog converter when the latter's output is looped back to the former's input. Its nonlinear function is created when at least one of the lines between the converters is cut and that which connects to the DAC is tied to a logical High. Other maps are produced when additional DAC input lines are similarly altered, or instead clamped to a logical Low. The resulting closed-loop systems exhibit several bifurcations including that which lead to pseudo-randomness. Simulation results from numerical analysis match fairly well with those derived from an electronic circuit realization. © 2010 Elsevier B.V.